TANGGUNG JAWAB LINGKUNGAN DAN PERSEPSI ANCAMAN EKOLOGI TERHADAP PERILAKU PRO-LINGKUNGAN KARYAWAN PERUSAHAAN DI DAS CITARUM KECAMATAN BABAKANCIKAO KABUPATEN PURWAKARTA PROVINSI JAWA BARAT - rita istiana (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2020)
This study aims to measure the relationship between corporate environmental responsibilityand the perception of ecological threats to the pro-environmental behavior of company employees. Itwas found that the environmental responsibility of the company had an effect on the pro-environmentbehavior of employees by 20.1%, which means that the role of the company to make rules or norms ofpro-environment behavior was still very low. The perception of ecological threats has an effect on thepro-environment behavior of employees by 33.7%, this explains that employees' knowledge ofecological threats is low and has not been able to provide awareness of the company's environmentalsustainability. The corporate environmental responsibility and the perception of ecological threatsaffect the pro-environment behavior of the company's employees by 34.3%. These results can explainthat the role of companies to educate their employees and the application of environmentalpreservation rules and norms needs to be further improved.